2006
DOI: 10.1542/peds.2005-0516
|View full text |Cite
|
Sign up to set email alerts
|

Pediatricians' Knowledge, Training, and Experience in the Care of Children With Fetal Alcohol Syndrome

Abstract: The survey confirms that pediatricians are knowledgeable about fetal alcohol syndrome but do not feel adequately trained to integrate the management of this diagnosis or prevention efforts into everyday practice. Furthermore, the respondents were not active in routine anticipatory guidance with adolescents for prevention of alcohol-affected pregnancies. The development, dissemination, and implementation of best practice tools for prevention, diagnosis, and referral of fetal alcohol syndrome that are specific f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 26 publications
(25 reference statements)
2
59
0
4
Order By: Relevance
“…24 Further, children's health providers do not routinely consider prenatal alcohol exposure in the differential diagnosis of behavioral and learning problems. 25 In the current study, ADHD was the most common referral diagnosis for children who ultimately were diagnosed with FASD. Previous studies have demonstrated that anywhere from 40% to 75% of children with FASD are diagnosed with ADHD.…”
Section: Discussionmentioning
confidence: 74%
“…24 Further, children's health providers do not routinely consider prenatal alcohol exposure in the differential diagnosis of behavioral and learning problems. 25 In the current study, ADHD was the most common referral diagnosis for children who ultimately were diagnosed with FASD. Previous studies have demonstrated that anywhere from 40% to 75% of children with FASD are diagnosed with ADHD.…”
Section: Discussionmentioning
confidence: 74%
“…To facilitate diagnosis and treatment of FASDs, it is imperative that professionals working in health care, education, social services, and the criminal justice system are properly trained in how to recognize individuals with PAE and educated regarding appropriate interventions for this population [Gahagan et al, 2006;FASD Regional Training Centers Consortium, 2007;Wedding et al, 2007;Mutch et al, 2009;Paley et al, 2009]. In some cases, it may also be important to change the attitudes of professionals who come in contact with and provide services to alcohol-exposed individuals and their families.…”
Section: Recommendations and Future Directionsmentioning
confidence: 99%
“…however, these data depend on cultural and social factors within each population regarding alcohol use by women, so that the actual rates may be at least tenfold increased in high risk populations. In addition, FAsd incidence rate may be extremely underestimated due to health workers' lack of knowledge [6][7][8] . It has been reported that at least 50% of Canadian and American women drink socially, and as half of all pregnancies are not planned, approximately 25% of newborns may have been exposed to alcohol in utero [9][10] .…”
mentioning
confidence: 99%